The Application of Artificial Intelligence (AI) in Vehicle Motion Mechanics Learning to Optimize Students’ Critical Thinking and Problem-Solving Skills - Doni Permana; Erni Masdupi (Jurnal Syntax Transformation, 2025)
This study examines the influence of working capital management on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from Q1 2020 to Q4 2024, with seasonality as a moderating variable. Working capital management is measured through Cash Conversion Cycle (CCC), Days Sales Outstanding (DSO), Days Inventory Outstanding (DIO), and Days Payable Outstanding (DPO), while financial performance is measured using Return on Assets (ROA) with leverage and firm size as control variables. Using a quantitative approach with panel data regression analysis and Moderated Regression Analysis (MRA), this study analyzes 100 quarterly observations from five transportation and logistics companies. The results show that CCC, DSO, and DIO have a significant negative effect on ROA, while DPO shows a positive but not significant effect. Seasonality significantly moderates the relationship between CCC, DSO, and DIO with ROA, indicating that seasonal variations strengthen the negative impact of working capital inefficiency on financial performance. These findings provide important implications for companies to optimize working capital management strategies by considering seasonal patterns in the transportation and logistics industry.